2015
DOI: 10.1111/twec.12287
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Financial Access: Is There Really a Link and for Whom? Evidence from Mexican Household Data

Abstract: In policy discussions, it has frequently been claimed that migrants' remittances could function as a ‘catalyst’ for financial access among receiving households. This paper provides empirical evidence on this hypothesis from Mexico, a major receiver of remittances worldwide. Using the Mexican Family Life Survey panel (MxFLS) for 2002 and 2005, the results from the fixed effects logit model show that receiving remittances is strongly correlated with the ownership of savings accounts and to a limited degree with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Remittances towards developed countries are not the primary interest of this paper; instead, the main incentives of remitting money to all countries and developing countries are explored. During recent years, different aspects of remittances towards developing countries have been under scrutiny of researchers, such as the growth impact of remittance (Barajas, Chami, Fullenkamp, Gapen, & Montiel, ; Giuliano & Ruiz‐Arranz, ; Rao & Hassan, ); the impact of remittances on poverty and inequality (Adams & Page, ; Acosta, Calderon, Fajnzylber, & Lopez, ); the impact of remittances on financial development (Aggarwal, Demirg‐Kunt, & Peria, ; Brown, Carmignani, & Fayad, ); the impact of remittances on current account (Hassan & Holmes, ); remittances and business ownership (Amuedo‐Dorantes & Pozo, ); remittances and financial access (Ambrosius, ); and the impact of education and gender on remittances (Cooray, ; Le Goff & Salomone, ). However, this paper focuses on the main determinants of remittances and more specifically the motivations behind remittances.…”
Section: Introductionmentioning
confidence: 99%
“…Remittances towards developed countries are not the primary interest of this paper; instead, the main incentives of remitting money to all countries and developing countries are explored. During recent years, different aspects of remittances towards developing countries have been under scrutiny of researchers, such as the growth impact of remittance (Barajas, Chami, Fullenkamp, Gapen, & Montiel, ; Giuliano & Ruiz‐Arranz, ; Rao & Hassan, ); the impact of remittances on poverty and inequality (Adams & Page, ; Acosta, Calderon, Fajnzylber, & Lopez, ); the impact of remittances on financial development (Aggarwal, Demirg‐Kunt, & Peria, ; Brown, Carmignani, & Fayad, ); the impact of remittances on current account (Hassan & Holmes, ); remittances and business ownership (Amuedo‐Dorantes & Pozo, ); remittances and financial access (Ambrosius, ); and the impact of education and gender on remittances (Cooray, ; Le Goff & Salomone, ). However, this paper focuses on the main determinants of remittances and more specifically the motivations behind remittances.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by Ambrosius (2015), Aggarwal et al (2011), Demirguc-Kunt et al (2011), Anzoategui et al (2011) the link between remittances and access to financial services by the recipients of remittances has received limited attention in academic literature. Of the studies that have been conducted in order to investigate the association between remittances and access to financial services, the apparent majority of these studies have found evidence of a positive relationship (Ambrosius and Cuecuecha, 2016;Ambrosius, 2015;Anzoategui et al, 2011;Aggarwal et al, 2011;Demirguc-Kunt et al, 2011;Gupta et al, 2009).…”
Section: Remittances and Financial Inclusionmentioning
confidence: 99%
“…Of the studies that have been conducted in order to investigate the association between remittances and access to financial services, the apparent majority of these studies have found evidence of a positive relationship (Ambrosius and Cuecuecha, 2016;Ambrosius, 2015;Anzoategui et al, 2011;Aggarwal et al, 2011;Demirguc-Kunt et al, 2011;Gupta et al, 2009). However, an outlying study by Brown et al (2013) did not find any evidence to support the claims of a positive relationship between remittances and the receiving households' use of formal banking services.…”
Section: Remittances and Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we extend and complement the literature on remittances-inclusive finance nexus by presenting for the first time, a cross-country evidence of the relationship between remittances and inclusive finance from the perspective of pension. Prior studies typically focus on access to banking services in the definition of inclusive finance (Ambrosius, 2016;Ambrosius and Cuecuecha, 2016;Le, Chuc and Taghizadeh-Hesary, 2019;Neaime and Gaysset, 2018). Additionally, whereas most studies focused on single country analysis (Cuadros-Meñaca, 2020; La and Xu, 2017), we study a panel of 96 countries from five regions, namely: (1) Africa, (2) Asia-Pacific, (3) Eastern Europe, (4) Latin America, and 5Western Europe and Others.…”
Section: Introductionmentioning
confidence: 99%